GOVERNANCE AND LEGITIMACY. PAST IN PRESENT - Dan VELICU (Challenges of the Knowledge Society)
Governance and legitimacy were two issues that generated long-standing political disputes in Europe. If legitimacy was grounded on the theory of divine rights during the Middle Ages, the idea of representation challenged the whole political system. Kings were interested in preservation of their political power as it was acquired during the earlier centuries meanwhile the parliaments were trying to become not a consultative body, but a legislative body. As a consequence, whenever the spirit of reconciliation of the great political actors lacked, the road to institutional conflict was opened. Sometimes the institutional conflict transformed itself in a civil war as it happened in seventeenth century England. Unfortunately, history proved that many times the constitution didn’t managed to solve the problem. Even though today such a matter has been solved in some democracies in other states, the two concepts have often blocked the good functioning of the central administration. As a special case the Organic Statutes of the Romanian Principalities were designed to set rules for at least some decades. Unfortunately, their authors were able to settle the rules regarding the prince as central authority and the National Assembly. The purpose of this article is to establish the conflicting moments between the two concepts under different constitutional regimes and how they have been solved in the modern history of Romania.